Inflammatory pseudotumor mimicking chronic pulmonary embolism or pulmonary artery sarcoma: Report of five cases. (29th December 2021) - Liao, Xiaoyan; Bojanowski, Christine M.; Yen, Andrew; Kerr, Kim M.; Dumouchel, Justin; Auger, William R.; Madani, Michael M.; Pretorius, Victor; Wang, Huan‐You; Yi, Eunhee S.; Lin, Grace Y.
Abstract: Inflammatory pseudotumor (IPT), also known as plasma cell granuloma, is a rare lesion of unknown etiology that occurs in many organs, especially in the lung. Here we report five cases of IPT arising in pulmonary artery mimicking chronic thromboembolic disease, not previously documented in the literature. Those cases were identified at our institute among over 2500 pulmonary endarterectomy (PEA) specimens acquired from 2000 to 2017. The cohort included three men and two women with a median age of 41 years (range: 23–54). All patients presented with dyspnea and radiologic findings of pulmonary artery thromboembolism, some concerning for intimal sarcoma. The duration between disease onset and PEA ranged from 6 months to approximately 3 years. Histologically, all cases showed proliferation of spindle cells with marked inflammatory infiltrates composed predominantly of plasma cells, histiocytes, and small lymphocytes. Ancillary studies were performed in each case and ruled out other possibilities, such as sarcoma, lymphoma, plasmacytoma, IgG4‐related disease, and infection. IPT arising in pulmonary artery presenting clinically as acute or chronic thromboembolic disease is very unusual, in which clinical data, radiographic findings, and histopathologic features have to be integrated for reaching the proper diagnosis.